Uncovering antiobesity-related hypertension targets and mechanisms of metformin, an antidiabetic medication. Issue 1 (1st January 2021) - Yang, Lu; Yang, Jianxin; Liang, Xiao; Huang, Wenjun; Zhang, Xiaoxi; Li, Rong
ABSTRACT: Metformin, a common clinical drug used to treat diabetes mellitus, is found with potential antiobese actions as reported in increasing evidences. However, the detailed mechanisms of metformin-antiobesity-related hypertension remain unrevealed. We have utilized the bioinformatics strategy, including network pharmacology and molecular docking analyses, to uncover pharmacological targets and molecular pathways of bioactive compounds against clinical disorders, such as cancers, coronavirus disease 2019. In this report, the in-silico approaches using network pharmacology and molecular docking was utilized to identify the core targets, pharmacological functions and mechanisms of metformin against obesity-related hypertension. The networking analysis identified 154 differentially expressed genes of obesity and hypertension, and 21 interaction genes, 6 core genes of metformin treating obesity-related hypertension. As results, molecular docking findings indicated the binding capability of metformin with key proteins, including interleukin 6 (IL-6) and chemokine (C-C motif) Ligand 2 (CCL2) expressed in obesity- and hypertension-dependent tissues. Metformin-exerted antihypertension/obesity actions involved in metabolic regulation, inflammatory suppression. And antihypertension/obesity mechanisms of metformin were revealed, including regulation of inflammatory and immunological signaling pathways for ameliorating microenvironmental homeostasis in targeting tissues. In conclusion, our current bioinformatics findings have uncovered all pharmacological targets, biological functions and signaling pathways of metformin treating obesity-related hypertension, thus promoting its clinical application in future. GRAPHICAL ABSTRACT: uf0001